(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
The article contains experimental studies and their results aimed at identifying and treating various pathologies of the esophageal mucosa due to gastroesophageal reflux disease (GERD). The experiments were carried out at the training center of the Department of experimental surgery of the State Institution "RSSPMCS named after Academician V. Vakhidov", and morphological studies in the pathoanatomic, morphological and scientific research department of this center. Our experiments were carried out on various animals (rodents and mammals) in order to treat changes in the mucous membrane of the esophagus, subsequently GERD. In the experiments, we used laser radiation, which is part of modern complex methods of treatment, while providing complete information about the stages of treatment and doses of laser radiation of pathological changes in the mucous membrane of the esophagus as a result of IR-diode laser irradiation.